Second stage caesarean section – the importance of regular audit. (18th April 2012) - Webster, LM; Cotzias, C
Abstract : Caesarean section in the second stage of labour is well documented to carry increased risk of morbidity.1 Complications include increased blood loss and surgical trauma.2 As such, it is important all maternity units audit their second stage caesarean sections and ensure clinical practice complies with local and national guidelines. We retrospectively audited the second stage caesarean sections performed during a six month period in a West London District General Hospital (47 cases, 1.6% of deliveries). The length of second stage, intra-operative surgical complications and seniority of those present at delivery were recorded. Awareness of the results was then raised through unit wide education. The hours of consultant cover on labour ward were also increased and a re-audit took place over two months (10 cases, 1.4% of deliveries). In the initial audit the most senior clinician available was not present in 13% of cases. This improved with the most senior clinician present at all deliveries and 80% of cases this was a consultant during re-audit. The intra-operative complication rate was 34% improving to 30% with our interventions. 7% of the initial cases required a transfusion, but none required transfusion in the repeat audit. The other improvement seen was a reduction in those staying more than 3 days, 23 down to 20%. These findings confirmed the published data regarding risks relating to second stage caesarean section. It also highlighted the importance of senior supervision and monitoring the length of second stage.